PENGARUH KEADILAN ORGANISASI DAN ETOS KERJA ISLAMI TERHADAP KOMITMEN ORGANISASI DAN KINERJA KARYAWAN PADA BMT SE-KABUPATEN KUDUS (Equilibrium: Jurnal Ekonomi Syariah, 2016)
This research used field research approach with questionnaire distributed to employees of BMT in Kudus, 105 respondents. Samples were taken using proportionate stratified random sampling and the data were analyzed using path analysis. The results were: 1) Justice of organization has positive influence and significant to organizational commitment with tcount 2,308 > ttable 1,982; 2) Islamic work ethos has positive influence and significant to organizational commitment with tcount 31,058 > ttable 1,982; 3) Justice of organization has positive influence and significant to employees performance with tcount  2,000 > ttable 1,982; 4) Islamic work ethos has positive influence and significant to employees performance with tcount 5,448 > ttable 1,982;  5) Organizational commitment has positive influence and significant to employees performance with tcount 2,340 > ttable 1,982.